ANALISIS MINAT BELAJAR SELAMA PANDEMI COVID-19 DI SMP NEGERI 1 BARUS - Suhetni Asmarita Situmorang; Mhd. Nau Ritonga; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2021)
The background of this research is Covid- 19 pandemic early 2020 that caused teaching learning process changed from offline become online. This case caused students’ activeness in learning is reduced. The aim of this study is to know students’ learning interest in Covid-19 pandemic period at seventh grade students of SMP Negeri 1 Barus. Questionnaire was used in collecting the data and subject consist of 26 students. The result of the research shows 34.61% is enough category (9 students), 11.24% is good category (3 students), 3.85% is very good category (1 student).